Supporting Student-Centred Teaching with New Media - Case Study and Experience Report - Motschnig-Pitrik, Renate (Proceedings of the International Conference on Networked Learning, 2002)
The Student-Centred Approach builds upon the theory that students who are given the freedom to explore areas based on their personal interests, and who are accompanied in their learning by a supportive, understanding facilitator not only achieve superior academic results but also grow personally and socially. However, pure Student-Centred teaching is more demanding in terms of time as well as learning material. The basic idea underlying our approach is to combine Carl Rogers' Student-Centred Teaching with the use of the Internet. The case study shows that this combination has the potential of reducing the increased efforts in the longer run, while fully retaining its benefits, most prominently deeper learning processes and a higher degree of flexibility, self-confidence, and social skills.